The Hidden Power of Patience in Athletic Success: A Comprehensive Narrative Review - Abdollahi Dehkordi, Amir Mohammad; Taheri, Morteza (Health Nexus, 2025)
Success in sport has traditionally been attributed to physical fitness, technical skill, and mental resilience, with grittiness—determination and passion for long-term goals—reigning supreme over the last decade. This narrative synthesis brings together recent research to position patience as an individual construct, and how it is used in performance enhancement, injury rehabilitation, learning of skills, and career duration. The review sets out to classify patience into three dimensions—interpersonal, life hardships, and daily hassles—and compares it with equivalent constructs like grit, self-control, and mental toughness. Dual-process theory and temporal motivation theory are the theoretical models used to describe patience's cognitive and motivational mechanisms. Patience has been found to have evidence for its effectiveness in enhancing decision-making, emotion regulation, and attentional focus, as well as moderating physiological stress and recovery from injury. Practical applications to coaches, athletes, and sport psychologists are discussed, and suggestions for enhancing patience with targeted interventions are presented. By completing the gaps in the literature, this review argues for more visibility for patience as a critical component of sporting success.